Super Man and the Bug Out - Doctorow, Cory, 1971- (Salt Lake City, UT : Project Gutenberg, 2005)
"Super Man and the Bug Out" by Cory Doctorow is a science fiction short story originally published in 2001, later featured in the collection "A Place So Foreign and Eight More," released in the early 2000s. The story explores themes of identity and responsibility through the lens of a superhero navigating a society transformed by the interstellar Bugout Federation, which promises peace and stability. In this unique narrative, Doctorow intertwines humor and cultural commentary, creating a rich tapestry reflecting contemporary social issues. The plot centers on Hershie Abromowicz, a superhero known as the Super Man, who grapples with his purpose in a world where his skills as a protector seem increasingly redundant. After the arrival of the Bugouts, who promise to end war and crime, Hershie finds himself facing a personal and societal crisis, questioning the nature of his identity and role. Through interactions with his mother, activist friends, and a new, challenging political landscape, he navigates the complexities of a world that no longer needs a traditional superhero. The climax unfolds at the DefenseFest 33 event, where Hershie confronts his beliefs and takes a stand against the military-industrial complex, ultimately embracing his identity while affirming the importance of self-determination in a transformed world. (This is an automatically generated summary.)
Release date is 2005-11-20
Keywords: Science fiction